2011
DOI: 10.1073/pnas.1012544108
|View full text |Cite
|
Sign up to set email alerts
|

Outcrossing, mitotic recombination, and life-history trade-offs shape genome evolution in Saccharomyces cerevisiae

Abstract: We carried out a population genomic survey of Saccharomyces cerevisiae diploid isolates and find that many budding yeast strains have high levels of genomic heterozygosity, much of which is likely due to outcrossing. We demonstrate that variation in heterozygosity among strains is correlated with a life-history tradeoff that involves how readily yeast switch from asexual to sexual reproduction under nutrient stress. This trade-off is reflected in a negative relationship between sporulation efficiency and pseud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
182
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(202 citation statements)
references
References 53 publications
20
182
0
Order By: Relevance
“…While we found trends in mating and multicellular growth within clades, the diverse array of phenotypes observed in wild and domesticated isolates likely reflects the plasticity of this species in response to stress and habitat variability (Kvitek et al 2008;Liti et al 2009). In agreement with Magwene et al (2011), about half of our sampled isolates showed a preference for either asexual or sexual reproduction; however, the other half readily switched between sexual and asexual growth when exposed to different growth media. Phenotypic plasticity can be an advantage for yeast living in habitats where resources or growth conditions fluctuate (Halme et al 2004;Avery 2006;Bishop et al 2007;Yvert et al 2013).…”
Section: Risk Factors For [Pin+] Infectionsupporting
confidence: 87%
See 3 more Smart Citations
“…While we found trends in mating and multicellular growth within clades, the diverse array of phenotypes observed in wild and domesticated isolates likely reflects the plasticity of this species in response to stress and habitat variability (Kvitek et al 2008;Liti et al 2009). In agreement with Magwene et al (2011), about half of our sampled isolates showed a preference for either asexual or sexual reproduction; however, the other half readily switched between sexual and asexual growth when exposed to different growth media. Phenotypic plasticity can be an advantage for yeast living in habitats where resources or growth conditions fluctuate (Halme et al 2004;Avery 2006;Bishop et al 2007;Yvert et al 2013).…”
Section: Risk Factors For [Pin+] Infectionsupporting
confidence: 87%
“…Like ancient, wild strains of S. cerevisiae sampled in primeval forests of China (Wang et al 2012), isolates from the ancestral clade showed the highest levels of inbreeding and reproductive isolation. Furthermore, strains from this clade had sporulation efficiencies that were similar to wild, undomesticated isolates sampled in forests and much higher than most domesticated isolates (Gerke et al 2006;Magwene et al 2011;Wang et al 2012). Of course, sporulation is not sufficient to ensure frequent outcross mating.…”
Section: Risk Factors For [Pin+] Infectionmentioning
confidence: 96%
See 2 more Smart Citations
“…First, clinically derived strains comprised 59% of the mosaic strains (P = 0.00233, Fisher's exact test). Clinical S. cerevisiae isolates tend to be multiply heterozygous (Muller and McCusker 2009a;Magwene et al 2011), consistent with outcrossing between different S. cerevisiae populations and the clinical origin-mosaic group association. Similarly, in the human pathogens Toxoplasma gondii and Cryptococcus gattii, outcrossing between different populations results in progeny with mosaic genomes that have increased transmission, dissemination, and/or virulence phenotypes (Grigg and Suzuki 2003;Minot et al 2012;Voelz et al 2013).…”
Section: Population-phenotype Associations In the 100-genomes Strainsmentioning
confidence: 65%